Effect of Root and Foliar Treatment of Marrow Plants with Copper Solutions on the Growth of Plants and on its Uptake of Copper and the Distribution of this Uptake in the Various Parts of Plant (Roots, Stem, Leaves, and Fruits) - Radi Dauod; M. M. Al-Subu; A. Atallah (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
In this study we have measured the effect of root and foliar treatments of marrow plants with 03 - 7.3 ppm copper solutions. Both types of treatment resulted in a substantial inhibition of growth of plant. This inhibition was compared for the various parts of plant (roots, stern, leaves and fruits) and for the two types of treatment. The concentration and the total content of copper in the various parts of treated plants were measured and compared with each other. The percentage of copper taken by plant from the total amount of copper added during the treatment of marrow plants was found to be very small. This percentage was found to be very small. This percentage was found higher in foliar - treated plants than in root - treated plants. It was also higher front dilute copper solutions than front more concentrated copper solutions.